Human Toxocariasis in Portugal-An Overview of a Neglected Zoonosis over the Last Decade (2010-2020) - Ana Margarida Alho; Pedro Manuel Ferreira; Isabel Clemente; Maria Amélia Afonso Grácio; Silvana Belo (MDPI AG, 2021)
Toxocariasis is one of the most widespread and important zoonotic parasitic diseases, although neglected. Data regarding human Toxocara infection in Portugal are almost absent. This article gives an overview of the situation of toxocariasis in Portugal over the last decade based on casuistic data. A total of 846 serum samples from individuals suspected of toxocariasis, collected from 2010 to 2020, were analyzed at the Institute of Hygiene and Tropical Medicine. Sera were tested for IgG antibodies to Toxocara canis excreted-secreted larval antigens by enzyme-linked immunosorbent assay and counterimmunoelectrophoresis. Positivity was detected in 18.8% (159/846) [CI 95%: 16.3-21.6], with positives detected throughout continental Portugal. Overall, 59.7% of the positives were diagnosed in younger than 20 years (35.2% aged 0-9 years and 24.5% aged 10-19 years). Eosinophilia was the most frequent feature reported (27.7%). Pediatrics (41.5%) and Infectiology (25.8%) were the specialties with the highest number of positives. An average of 77 samples/year were received, recording a maximum positivity in 2012 (41.5%, n = 27/65) and a minimum in 2020 (6.4%, n = 3/47). These numbers may reflect the effectiveness of current preventive measures, highlighting the need to maintain public awareness to control this helminthozoonosis and promote a higher public health standard.